Integrating PV plant 689 kWp into Coal-Fired Power Plant (CFPP) 615 MW at Paiton: To reduce auxiliary load and coal consumption - Albar, Syarief; Windarta, Jaka; Wardaya, Asep Yoyo; Elshaarani, Tarig (Universitas Negeri Padang, 2022)
Integrating solar energy into a coal-fired power plant is a promising way to reduce auxiliary load and numerous environmental issues related to the coal-based power generation sector. This paper will discuss the annual performance of PV plant 689 kWp at ash disposal that integrated into 615 MW coal-fired power plant PT xxx, including an estimate of total potential energy that can be generated; analysis of auxiliary load to improve performance and decreasing pollutant emissions by coal consumption reduction. The PV Plant has been operated for at least 2 years, built on an area of 5,000m2, is an On-grid PV Plant system with 11 grid Inverters and has 2,120 solar modules installed. Based on the simulation using Helioscope software, it can generate electrical energy up to 977,442 kWh per year with a performance ratio of 79.3%. The result of the PV plant utilization evaluation shows the amount of electrical energy produced is 1,096,105 kWh in 2021, above the estimation from the simulation. This result means auxiliary power load was decreasing by 0.4932%, It is also considered to be able to save the use of 263.065 kiloliters per year of diesel and also save the use of coal up to 386.634 tons or equivalent to 0.007% coal consumption per year. From an environmental point of view, it is also assessed to reduce CO2 emissions equivalent to 920.729 tons/year and the equivalent of planting 4,602 trees per year.